Nomadic indigenous peoples and the law - Sigamany, Indrani, author.
1 online resource.
Keywords: "This book investigates the unique challenges faced by nomadic Indigenous Peoples in claiming self-determination and rights to their ancestral lands. Nomadic or mobile Indigenous peoples have been largely ignored in the wider context of In-digenous land rights, but such groups often even more marginalised than other Indigenous Peo-ples. Focusing on the Indian Forest Rights Act, this book explores how access to justice re-mains uneven and elusive for mobile Indigenous communities who have been dispossessed of their lands. Exposing the lack of recognition of usufruct rights and of customary land laws, which have caused a more acute displacement from ancestral lands for mobile Indigenous Peo-ples, the book reveals how their nomadic livelihoods have excluded them from government policies and laws. The book further examines the gendered and intersectional aspects of this exclusion. In conclusion, the book maintains that legislation such as the progressive Forest Rights Act is necessary, but not enough, to protect the rights of mobile Indigenous Peoples. In such cases, the book argues, legislation has to be supported by nuanced governance, which is sensitive to the particular challenges presented by Indigenous peoples who are further marginal-ised through nomadic lifestyles. This book will be of interest to scholars and researchers working in the areas of Indigenous Studies, Socio-legal Studies, Human and Minority Rights, and Gender and International De-velopment"-- Provided by publisher.